(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2022)
This paper presents a flexible rectenna for RF energy harvesting application. The textile wideband antenna is designed using CST software. The Fleece and Shieldit fabrics are used as substrate and conductive material, respectively. The antenna is fabricated and its measurement performances are described in terms of reflection coefficient and the radiation pattern is measured. Then, the rectifier circuit is designed and simulated using ADS software and the integration between antenna and rectifier (rectenna) is achieved using the same software. The flexible rectenna is experimentally verified at different distances from the RF source. The highest measured DC output voltage is 35 mV at a distance of 0.5 m. The system harvests DC output voltage successfully even though it only produces a small value. This system can be improved more and used for obtaining continuous energy for future wearable applications.